THE COMMUNICATION STRATEGY OF THE CIVIL SERVICE POLICE UNIT IN THE RELOCATION OF TRADERS AT ANYAR MARKET, TANGERANG CITY, BANTEN PROVINCE - Barokah, Siti Ikpini Rizkiyatul; Aprimawati, Baiq (Jurnal Tatapamong, 2024)
The objectives to be achieved in this study are to analyze and describe the Communication Strategy of the Tangerang City Civil Service Police Unit Banten Province to Anyar Market Traders; analyze and describe the supporting factors and inhibiting factors in the Communication Strategy of the Tangerang City Civil Service Police Unit Banten Province to Anyar Market Traders; analyze and describe the efforts that hinder the Communication Strategy of the Tangerang City Civil Service Police Unit Banten Province to Anyar Market Traders. The research design used is a qualitative descriptive approach, the data collection techniques used are interviews, documentation and observation. The theory used by the author is the theory of strategy according to James Briann Quin which has dimensions including goals, policies and programs. The results of the study show that the Communication Strategy of the Civil Service Police Unit in the relocation of Anyar Market traders in Tangerang City has been running well and succeeded in moving the Anyar market traders to the relocation site provided, this has been described in accordance with the dimensions and indicators of the theory that the author uses, by having a communication strategy used by the Tangerang City Government such as bidding, socialization and dialogue with Anyar Market Traders which is carried out in accordance with conditions in the field and prioritizes the common interest. The inhibiting factors are that the relocation places are far apart; the existence of provocateurs. Supporting factors are, 1) Good coordination and communication with the agencies involved such as PD. Market, Indagkop, Tangerang City Metro Police, Transportation Department, Environmental Service, Kesbangpol 2) have various ways to approach such as wawaran by notifying the Traders by using cars and loudspeakers for sounding related to relocation, socialization by providing direct understanding regarding the process of moving to the relocation site and dialogue with the Anyar Market Traders regarding the obstacles faced. Keywords: Communication strategy; Civil Service Police Unit; Traders Relocation.